Strategi Komunikasi Global Radio 88.4 FM Jakarta dalam Memelihara Eksistensi sebagai Radio Anak Muda - Vivian Aprilia; Elpa Hermawan; Ondy Ondy (Jurnal Ilmu Komunikasi, Administrasi Publik dan Kebijakan Negara, 2025)
This study aims to analyze the communication strategy implemented by Global Radio 88.4 FM Jakarta in maintaining its existence as a youth radio amidst the rapid growth of digital media. Using a descriptive qualitative approach, the study collects data through in-depth interviews, observations, and documentation. The data obtained is analyzed using Cangara's communication strategy theory and George R. Terry's POAC (Planning, Organizing, Actuating, Controlling) management theory. The results show that Global Radio 88.4 FM Jakarta implements several key strategies, including program segmentation to meet the needs of young audiences, optimizing the use of social media such as TikTok and Instagram, and strengthening emotional relationships with listeners. The success of these strategies is influenced by well-planned content, efficient team organization, and flexible execution that responds to trends among the youth generation. However, amidst the growing competition in the digital world, challenges faced include changes in media consumption patterns and limited resources. This study provides insights into the importance of adapting communication strategies to maintain the existence of traditional radio in the digital era.